(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
The article is based on the diplomatic documentation that the representatives of the Austrian Empire in Madrid sent to Vienna between 1808 and 1825. Although they would refer to the events in Mexico, they didn’t describe them as independence movements. Until 1820 they didn’t show the conviction of a real and absolute independence, but from 1822 on they already made it clear that the situation had changed to the point of even thematize the recognition of the independence. The latter became widespread in Europe after 1823 and made America a subject of the monarchical politics of the time.